(untitled) (Revista Lusófona de Educação, 2013)
The main thesis of this paper is that Freire’s original experience in Angicos anticipated a grand design for social transformation of educational systems.As such it brought together two key concepts that formulated the basis of his educational system: popular culture as an counter-hegemonic project and popular education, more particularly what was later called citizen schools or public popular education as keystone of his new educational system.I use the term Paulo Freire System to show that his original attempts were not only to challenge pedagogical the prevailing banking education system that was so pervasive in Brazil and Latin American at the time. In challenging the hegemony of banking education, its narrative, theoretical foundations, epistemology and methodology, Freire and his team sought to create a new system that could replace the old one. They saw banking education not only as obsolete in terms of modernization of systems but also oppressive in gnoseological, epistemological and political terms. In the conclusion of this paper I will discuss the twins obsessions of Freire, already present in the Angicos experience and that will stay with him throughout his life: the relationship between democracy,citizenship and education, and education as a postcolonial ethical act of social transformation. I would like to emphasize therefore that the Paulo Freire system, as conceived in the Angicos experience and its after math was a much larger and comprehensive system that originally considered, even by his critics. Key-words: Angicos; social transformation; banking education; oppression; postcolonial education.